2016
DOI: 10.1038/cddiscovery.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Sundew plant, a potential source of anti-inflammatory agents, selectively induces G2/M arrest and apoptosis in MCF-7 cells through upregulation of p53 and Bax/Bcl-2 ratio

Abstract: The worldwide cancer incidences are remarkable despite the advancement in cancer drug discovery field, highlighting the need for new therapies focusing on cancer cell and its microenvironment, including inflammation. Several species of Drosera (family: Droseraceae) are used in various traditional as well as homeopathic systems of medicine. Drosera burmannii Vahl. is also enlisted in French Pharmacopoeia in 1965 for the treatment of inflammatory diseases, including chronic bronchitis, asthma and whooping cough.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…A large number of proteins operate in concert to regulate apoptosis. Bcl-2 is of particular interest as it has been reported to be protective against oxidative stress, reducing cell death induced by reactive oxygen species [7880]. Previous studies have shown that cells overexpressing anti-apoptotic Bcl-2 exhibit a marked reduction in apoptosis, which suggests that anti-apoptotic Bcl-2 could independently affect the rate of apoptosis [81].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of proteins operate in concert to regulate apoptosis. Bcl-2 is of particular interest as it has been reported to be protective against oxidative stress, reducing cell death induced by reactive oxygen species [7880]. Previous studies have shown that cells overexpressing anti-apoptotic Bcl-2 exhibit a marked reduction in apoptosis, which suggests that anti-apoptotic Bcl-2 could independently affect the rate of apoptosis [81].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h, cells were subjected to compound 1 or 2 at the concentration of 50 μM for another 24 h. Cells then treated with LPS (500 ng/ml) (Sigma, MO) for 12 h. Subsequently, cells were harvested and extracted for analysis. The quantifification of mRNA in macrophage cells was performed using a previously standardized method 21,22 .…”
Section: Concise Synthesis Of Compounds 1 Andmentioning
confidence: 99%
“…77 Trans-9-hexadecen-1-ol was found in EARE (1.85%) and traces in EALE (0.30%), it shows anti-inflammatory and anticancer activity. 78 Quercitol or 1-deoxy Inositol is a cyclic polyalcohol found in MRE (2.26%) which works as a powerful osmolyte and helps in drought stress tolerance in plants. 79 Hydrocarbons 12 different hydrocarbon compounds were detected in different extracts of L. reticulata.…”
Section: Alcoholic and Phenolic Compoundsmentioning
confidence: 99%